问题 解答题

若函数f(x),g(x)满足g(x-y)=g(x)g(y)+f(x)f(y),并且f(0)=0,f(-1)=-1,f(1)=1.

(1)证明:f2(x)+g2(x)=g(0).

(2)求g(0),g(1),g(-1),g(2)的值.

(3)判断f(x),g(x)的奇偶性.

答案

(1)证明:令y=x,g(0)=f2(x)+g2(x);

(2)∵g(0)=g2(0)+f2(0),

∴g(0)=0或1;

若g(0)=0,则由(1)可知f(x)=g(x)=0,与题设矛盾,

故g(0)=1.

又g(0)=g(1)g(1)+f(1)f(1),

g(0)=g(-1)g(-1)+f(-1)f(-1),

故g(1)=0,g(-1)=0,令x=1,y=-1,

g(2)=g(1)g(-1)+f(1)f(-1),g(2)=-1.

(3)g(y-x)=g(y)g(x)+f(y)f(x)=g(x-y),

故g(x)是偶函数;

用-x,-y 替换x,y,g(y-x)=g(-x)g(-y)+f(-x)f(-y),g(x)是偶函数,

与原式联立可得f(-x)f(-y)=f(x)f(y),令y=1,可得f(x)=-f(-x).

∴f(x)是奇函数.

单项选择题
单项选择题